CK prognostic factor in fast/slow progressive Amyotrophic Lateral Sclerosis (ALS). Issue 1 (January 2019) - Pozzilli, V.; Ceccanti, M.; Di Bari, S.; Fiorini, I.; Fanella, G.; Petrucci, A.; Di Maria, G.; Inghilleri, M.
Abstract : To measure serum creatine kinase (CK) and myoglobin in ALS and Chronic Inflammatory Demyelinating Neuropathy (CIDP) patients with secondary axonal damage to investigate mechanisms of muscular damage and to assess whether CK in ALS is correlated with clinical features and disease progression. CK and myoglobin were quantified in 116 ALS and 46 CIDP. Patients with ALS were followed for 20 months, subdivided in fast or slow disease progressors according to mean monthly reduction of functional scale (ALSFRS score), whereas CK was measured at different times. Relationship with onset site, proximal and distal nerve compound action potential (cMAP) was analyzed. At baseline CK was raised in ALS patients with spinal compared to bulbar onset. CK in CIDP patients was normal. Myoglobin was normal in both diseases. Slow progressive patients showed higher CK than fast progressive (p < 0, 05); a logarithmic correlation was found between CK and ALSFRS score over time. However, CK was not associated with cMAP measurements. CK was raised in ALS patients but not in those with neuropathic axonal damage. Energetic upregulation by the muscle but not a denervation process may be suggested. High CK, being linked to slow disease evolution, might be used as a marker.